Ryan McGinness works paintings, sculptures, sketches, drawings, installations, editions and other stuff - Armetta, Amoreen (New York Rizzoli, 2009)
From the Publisher: Ryan McGinness is an internationally exhibited artist whose skate-punk aesthetic incorporates carefully rendered personal iconography, contemporary semiotics, and layered neo-baroque compositions. His works are in multiple mediums and his signature symbols and visual code have influenced an entire generation of graphic designers. Ryan McGinness Works is a collection of the artist's most recent pieces, including installations, prints, sculpture, and paintings. Each body of work is illustrated and discussed in lavish detail, and the process behind each project is told through the use of sketches, diagrams, details, and photographs.
Texts. Interview / Peter Halley and Ryan McGinness -- Inside the studio: notes from a former assistant / Greg Lindquist -- Conversation / David Byrne and Ryan McGinness -- The look of looks, or, Ryan McGinness's ontology of color / Jonathan T.D. Neil -- Sketches and drawings -- Silkscreen, letterpress & lithography -- Installationview -- Varied editions -- Have you seen hime? -- Sculptures -- Paintings & installations -- The Q&A 500 / Tom Greenwood and Ryan McGinness.
Includes index.
FA-2995g donated by Ricky V.
Keywords: McGinness, Ryan -- Catalogs; McGinness, Ryan -- Criticism and interpretation; McGinness, Ryan -- Interviews; McGinness, Ryan